Implementasi Kesehatan Matra sebagai Upaya Kesiapsiagaan dan Manajemen Korban dalam Penyelenggaraan Festival Musik - Darmareja, Rycco; Hasan, Melani Meta; Hermawati, Risma; Maulida, Mutia; Putri, Annisa Rahma Cahya; Alifa, Salsa Bila (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Organizing a music festival will cause crowds in public spaces. This condition often creates serious safety and health problems and must be of concern to organizers as a form of responsibility in anticipating fatalities and injuries due to crowds. Aim: This community service program aims to increase preparedness in the form of knowledge, attitudes, and skills of participants regarding the introduction of safety and first aid to victims during music festivals. Methode: The method used is education and training in the form of providing safety introduction education and victim aid management during music festivals. Participants consisted of 36 people from the FARINGFEST committee, Faculty of Engineering, UPN